The Use of Artificial Intelligence in Teaching Writing Skills - Rosdiana, Siti; Noercolies, Muhammad Andreansyah; Fauzan, Muhammad Hendrie (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2024)
Technology has entered the educational sphere, particularly in the learning of foreign languages. The usage of artificial intelligence helps students' learning. Artificial intelligence, particularly in the writing process, can bring convenience by swiftly supplying references, paraphrasing sentences, and now checking sentence structure, which will undoubtedly improve students' writing abilities. This study used a descriptive qualitative method. This strategy seeks to provide a comprehensive and detailed description of numerous events. This study employs purposive sampling to collect data. Participants in this study are English Language Study Program students in the academic year 2023/2024 who apply artificial intelligence in their writing. Data was collected through interviews, observations, and documentation. The data analysis revealed that the most popular artificial intelligence tools among students are Quill Bot, Grammarly, Chat GPT, Deep L, Perplexity AI, and Essay Writer. Most students employ artificial intelligence during the writing process, particularly when brainstorming and drafting. Because they believe there is an urgent need for artificial intelligence in the process of finding references and composing a sentence into a paragraph, a student requires it. However, according to study, they continue to employ artificial intelligence in its natural stages, with pupils using it based on their needs and talents.